2020
DOI: 10.3390/ijerph17165846
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Hospital Performance Rated by Physicians in China: A Moderated Mediation Analysis on the Role of Income and Person–Organization Fit

Abstract: This study tested the effect of person–organization fit (P-O fit) in mediating the link between job satisfaction and hospital performance with income as a moderator. A questionnaire survey was conducted on 301 physicians from two public hospitals in Zhejiang province of China. Respondents were asked to rate their job satisfaction, value congruence (P-O fit) with the hospital, and the hospital’s performance. The mediating effect of P-O fit on the link between job satisfaction and hospital performance was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…Empirical evidence shows that low income is associated with low employee satisfaction. 34 A high workload is usually blamed for driving the deterioration of QWL. 2 31 Professional title is deemed as a proxy indicator of career success.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical evidence shows that low income is associated with low employee satisfaction. 34 A high workload is usually blamed for driving the deterioration of QWL. 2 31 Professional title is deemed as a proxy indicator of career success.…”
Section: Methodsmentioning
confidence: 99%
“…So he believed the individual organization fit referred to the consistent values beyond the individuals and the organizations. Later, more and more scholars have studied the personal and organizational values and found that the compatibility between the individual and the organization could have an impact on the employees’ job performance, organization commitment, and turnover [ 34 – 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Mosadeghrad, it was shown how quality management could affects employees. A well developed, well introduced and institutionalised quality management model can improve employees' job satisfaction [26][27][28]. It might also be noted that, in our current study, we studied the relationship of job satisfaction and organization's quality management level of three maternity hospitals.…”
Section: Discussionmentioning
confidence: 88%